Early Empathy: Impact of Digital Storytelling, Traditional-Storytelling, and Gender on Early Childhood - Maranatha, Jojor Renta; Wulandari, Hayani; Briliany, Noviarta (JURNAL PENDIDIKAN USIA DINI, 2024)
Stories are good media for enhancing emotional intelligence and empathy. Therefore, early childhoods know how to empathize with the figure of the story through storytelling. This research objective is to investigate the impact of digital storytelling and traditional storytelling as a learning media and gender on empathy in early childhood. This research is experimental with treatment by level 2 x 2 research design. The data collection instrument uses an observation sheet in the form of an early childhood empathy Rating Scale. The results of this research showed children who got the digital storytelling intervention had more empathy than children who got the traditional storytelling. Moreover, digital storytelling is more suitable for fostering empathy in the male gender compared with traditional storytelling. On another hand, traditional story-telling is more suitable for enhancing empathy in the female gender.